Study of myocardial deformation ascular magnetic resonance in patients with hypertrophic cardiomyopathy - O’Neill, Catarina Martins (2019)
Trabalho Final do Curso de Mestrado Integrado em Medicina, Faculdade de Medicina, Universidade de Lisboa, 2017